Universal precaution: practice among doctors in a tertiary care hospital in Manipur - Chaudhuri, Susmita; Baidya, Omkar Prasad; Singh, T. Gambhir (International Journal of Research in Medical Sciences, 2016)
Background: Health workers especially doctors are always at higher risk of exposure to blood borne pathogens in day to day practice. Universal precaution is the only strategy so that all these infections could be prevented. The objective of the study was to assess the practice of Universal Precautions among doctors & factors influencing its use in a tertiary health centre of Manipur. Methods: Cross-sectional study was conducted among the doctors in a tertiary health care centre of Manipur during October 2011 to September 2013. Structured questionnaire was used to collect data. Descriptive statistics like percentage was used to describe the findings using SPSS 20. Results: Total respondents were 366 doctors. Response rate was 98%. Total of 125 (34.2%) respondents always used glove as a measure of universal precaution. Hand-washing after removal of gloves was practiced by more than half of the respondents. Around 2 in 10 participants never used personal protective equipments like gown & mask. Around 7 in 10 participants always practiced recapping after use. Total of 150 respondents (41%) used to dispose sharps in sharp and liquid proof container with removing syringe.74.3% mentioned the reasoning of not practicing universal precaution was lack of supply of personal protective equipment. A total of 50 respondents told that emergency situation was also responsible for not adhering to the practice. Work stress (1.6%), time constraint (5.7%), lack of display of guidelines (3.8%) were the reasons mentioned by few of them. Conclusions: Universal precaution practice was poor. Training of the health care workers, proper equipment supply, posters displaying guidelines and proper hospital policy of patient load management would help in improving the implementation of universal precaution thus restoring occupational safety of health care workers.